SENSORY CHARACTERISTIC AND NUTRITIONAL CONTENT ONDE-ONDE KETAWA WITH JALEJO FLOUR (A MIXTURE OF CORN, SOYBEAN AND MUNG BEAN) - Farah Levyta (Jurnal Hospitality dan Pariwisata, 2017)
Corn, soybean and mung bean are known as source of vegetable nutrition, and combined in onecomposite material, they become a good source of complete essential amino acid. However, it isnot yet widely used in market. The Jalejo is able to be used in various bakings, one of them isOnde-onde Ketawa (‘Laughing Onde’). Onde-onde Ketawa is a distinctive Indonesian snackwith unique round shape covered in sesame, fried to make the surface crack and resembleslaughing expression. The ingredients are flour, egg, sugar, oil, water, baking powder andbaking soda, and sesame. This research is intended to find out sensory characteristics,particularly panellists reactions, to the substitution of this snacks’ ingredients with Jalejo. Thewriter used experiment method with standard recipe as a reference with 100% flour, comparedwith three executions: 75% Jalejo and 25% flour; 50% Jalejo and 50% flour; and 100% Jalejo.Research showed the 75% Jalejo combination was the panellists’ most favourable, and 50%Jalejo combination most likely had the same characteristics as the one with 100% flour.Keywords: Jalejo Flour, Onde-onde Ketawa, Sensory Characteristics